The Cajuns : Americanization of a people - Bernard, Shane K. (University Press of Mississippi, 2003)
History -- Southern Studies-- & . The past sixty years have shaped and reshaped the group of French-speaking Louisiana people known as the Cajuns. During this period they have become much like other Americans and yet have remained strikingly distinct. The Cajuns: Americanization of a People explores these six decades and analyzes the forces that had an impact on Louisiana's Acadiana. In the 1940s, when America entered World War II, so too did the isolated Cajuns. Cajun soldiers fought alongside troops from Brooklyn and Berkeley and absorbed aspects of new cultures. In the 1950s as rock 'n' roll.